Numeracy Literacy through Mystery Boxes: A Pedagogical Tool for Improving Multiplication Skills - Wulan Berliana Putri; Muhammad Noor Kholid (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the learning needs of fourth-grade elementary school students in multiplication and identify how the Mystery Box game can be used as a pedagogical tool to improve students' numeracy skills.Methodology: This study uses a qualitative approach involving students and teachers as research subjects. Data collection was conducted through observation, interviews, and analysis of documents/learning needs questionnaires.Results: The results showed that most students needed concrete learning support rather than just focusing on memorization. Teachers assessed that the Mystery Box game had great potential to help students build conceptual understanding through activities.Applications/Originality/Value: This study provides practical contributions to the development of mathematics learning in elementary schools, especially in multiplication material. The use of Mystery Box is said to be able to provide a more concrete, interactive, and enjoyable learning experience so that it can be applied as an alternative learning strategy.